2008
DOI: 10.1007/s11274-008-9886-0
|View full text |Cite
|
Sign up to set email alerts
|

Solid-state fermentation-supported enhanced production of α-galactosidase by a deoxyglucose-resistant mutant of Aspergillus niger and thermostabilization of the production process

Abstract: The aim of the present investigation was to comparatively evaluate the behaviour of A. niger and its derepressed mutant in production of a-galactosidase in submerged (SmF) and solid state fermentation (SSF) using basal Vogel's medium or corn steep liquor as nitrogen source and observe the response of latter source under both cultural techniques under different temperature regimes, and determine if SSF can be exploited in a wide range of temperature expected to vary in this fermentation system. All studies were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…Awan et al (2009) has also reported change in enthalpy (21.6 and 19.1 kJ/mol) and entropy (-134.3 and -138.4 J/mol/K) of parent and mutant A. niger, respectively for αgalactosidase production in solid state fermentation using wheat bran supplemented with glucose as carbon source and corn steep liquor as a nitrogen source. Low magnitudes of activation energy, enthalpy, Gibbs free energy and entropy for product formation are considered to be indices for thermostability of metabolic pathway (Rajoka et al, 2009). Therefore, we suggest that the mutation had significant effect in thermostabilization of the metabolic network of mutant (M6) during BGL production, which might be due to either formation of chaperons or hyperglycosylation of enzymes of the production metabolic network as reported earlier (Aiba et al, 1973).…”
Section: Kinetics and Thermodynamics Of Bgl Production On Wheat Bransupporting
confidence: 73%
See 2 more Smart Citations
“…Awan et al (2009) has also reported change in enthalpy (21.6 and 19.1 kJ/mol) and entropy (-134.3 and -138.4 J/mol/K) of parent and mutant A. niger, respectively for αgalactosidase production in solid state fermentation using wheat bran supplemented with glucose as carbon source and corn steep liquor as a nitrogen source. Low magnitudes of activation energy, enthalpy, Gibbs free energy and entropy for product formation are considered to be indices for thermostability of metabolic pathway (Rajoka et al, 2009). Therefore, we suggest that the mutation had significant effect in thermostabilization of the metabolic network of mutant (M6) during BGL production, which might be due to either formation of chaperons or hyperglycosylation of enzymes of the production metabolic network as reported earlier (Aiba et al, 1973).…”
Section: Kinetics and Thermodynamics Of Bgl Production On Wheat Bransupporting
confidence: 73%
“…The ΔS* (x) and ΔS* (p) for cell mass and BGL production were also determined. The thermodynamic growth parameters in submerged fermentation of the mutant were even lower than reported for thermotolerant Kluveromyces marxianus, Humicola lanuginosa (Bokhari et al, 2008) and A. niger NIAB 280 (Rajoka et al, 2009). Awan et al (2009) has also reported change in enthalpy (21.6 and 19.1 kJ/mol) and entropy (-134.3 and -138.4 J/mol/K) of parent and mutant A. niger, respectively for αgalactosidase production in solid state fermentation using wheat bran supplemented with glucose as carbon source and corn steep liquor as a nitrogen source.…”
Section: Kinetics and Thermodynamics Of Bgl Production On Wheat Branmentioning
confidence: 57%
See 1 more Smart Citation
“…For micropropagule production, 40 g of zeolite moisturized by distilled water containing Vogel's salts (26)(27)(28) was used. Investigations of glucose concentration as a carbon source and supplementation of the production medium with various nitrogen sources including yeast extract, soybean flour, peptone, corn steep solids (CSS), and inoculation were performed by exactly the same procedure as described for the natural substrates.…”
Section: Culture Conditions For Inert Supportmentioning
confidence: 99%